TECHNOLOGICAL SOLUTIONS OF ROAD CHARGING SYSTEM - Ondrus, Jan; Dicova, Jana (Doprava a spoje, 2011)
Traffic congestion is an unpleasant problem felt by residents of most urban areas. With transport problems such as congested streets we can meet today nearly in every bigger city. It's an issue in cities worldwide: too many cars on too few roads. It arises from the main issue - an increase of individual car traffic in the city centre. The road charging in urban areas is very simple and efficient way to reduce traffic volumes, lower congestions or to limit individual transportation demand in the centres. In recent years, in developed countries (e.g. Stockholm, London) road charging system is playing more important role when solving traffic problems in cities. In our contribution we would like to focus on technological solution of road charging in urban areas, specifically on successful DRSC system in Stockholm.